The Impact of Campus Teaching Programs on Elementary Students' Literacy Skills - Runa Iqlima Nur Azizah; Yasinta Mahendra (MIMBAR PGSD Undiksha, 2025)
The Covid-19 pandemic has brought new challenges to the world of education, especially in relation to low literacy skills among students. Data from various international studies show that the literacy level of Indonesian students is still low. In the field, there are still many schools with inadequate literacy facilities and no structured literacy strengthening activities. The purpose of this study was to examine the impact of Kampus Mengajar on improving student literacy in elementary schools. This study used a method with a pre-experimental design, a one group pre-test and post-test model. The sampling technique in this study was a side-saturated technique with data collection techniques through pre-test, post-test, observation, interviews, and literature reviews. The results showed a p-value of 0.224 (p <0.05), which indicates a significant influence on students' literacy skills. Findings from interviews and observations showed improvements in three areas: library visits (from 15% to 60%), reading comprehension (from 35% to 80%), and letter recognition (from 10% to 55%). The study concluded that the Kampus Mengajar program showed a positive impact on student literacy and provided recommendations for the development of more effective education policies, especially in areas with difficulty in accessing quality education. The implications of this SLR study indicate that campus teaching programs have significant potential to improve students' literacy skills in elementary schools. The results of the study can provide insights for curriculum developers and educators to design more effective programs, as well as encourage collaboration between higher education institutions and elementary schools.